Insight Into Use and Safety of Mosquito Repellents; An Online Survey - Qurat ul Ain; Zilli Huma; Hassan, Wajahat; Rashid, Habiba (ADVANCES IN BASIC MEDICAL SCIENCES, 2024)
Objectives: To evaluate the public knowledge, attitude, and awareness regarding the safe use and side effects of commercial and natural mosquito repellents. Methodology: An online survey was conducted using a twelve-question questionnaire created on Google Forms. Public awareness about mosquito repellents and their safe use and side effects was assessed. The data was collected anonymously using social media platforms. The form was distributed using social media among individuals. We got 278 responses to the questionnaire. The survey results were downloaded from Google Forms in the Excel spreadsheet. Results were presented in the form of percentages. Results: The results showed that 86% of the respondents used commercial mosquito repellents while 61% of the participants did not have any idea about natural mosquito repellents. 63% of respondents were using commercial mosquito repellents in well-ventilated spaces and for 6-8 hours duration.75% were females who suffered from any kind of side effects after the use of mosquito repellents in which 58% were allergic reactions due to mosquito repellents while 61% of the respondents have a headache following use of mosquito repellents. Conclusion: Mosquito repellents can cause some adverse effects in the general public. Therefore, people should practice using these repellents in well-ventilated spaces up to 6-8 hours. Public health interventions are needed to minimize exposure to mosquito repellents and public awareness programs should be conducted.